Continuous straw return for 8 years mitigates the negative effects of inorganic fertilisers on C‐cycling soil bacteria. (30th November 2022) - Zhang, Qian; Guo, Tengfei; Sheng, Kai; Shi, Wenxuan; Han, Yanlai; Wang, Yilun; Li, Hui
Abstract: To elucidate the identity and mechanisms by which specific bacterial members drive efficient decomposition and utilisation of straw, the succession and co‐occurrence patterns of 13 C‐labelled bacteria were analysed using DNA‐stable isotope probing (SIP) techniques. Microcosms with 13 C‐labelled maize straw incorporated into soils subjected to no nitrogen (N) fertiliser (CK), chemical fertiliser (NPK) and chemical fertiliser with straw return (NPKS) treatments for 8 years were incubated for 360 days. The results showed that fertilisation regimes changed the 13 C‐labelled bacterial groups by abundance but not taxonomic composition, where N fertiliser application (NPK and NPKS treatments) reduced the relative abundance of maize straw carbon assimilators affiliated with Arthrobacter, Sphingomonas, Streptomyces, Burkholderia‐Caballeronia‐Paraburkholderia and Kribbella, but increased the relative abundance of Nocardioides, Rhodanobacter, Granulicella and Chujaibacter . Compared with CK and NPKS‐treated soils, continuous inorganic fertilisation reduced the α‐diversity of the 13 C‐labelled bacterial community and resulted in a loose and less competitive co‐occurrence network of straw C‐assimilators with more hubs needed to sustain its structural stability. Interestingly, straw return mitigated the negative effects of inorganic fertilisation by forming a tight and complex co‐occurrence network of maize straw utilizers associated with NPKS‐treated soils. Taken together, we emphasise the vital function of long‐term straw return for sustaining soil biodiversity under intensive fertilised agricultural conditions and provide reference bacterial members for efficient straw utilisation. Highlights: DNA‐SIP enabled the concise identification of straw C assimilating bacterial members. Inorganic fertilisation reduced straw C‐utilizer community diversity and their interactions. Straw return mitigates the negative effects of inorganic fertilisers on straw C‐cycling bacteria. Varying taxa sustained the interaction network of straw C‐utilizers in different fertilised soils.